2022
DOI: 10.1029/2021jc018309
|View full text |Cite
|
Sign up to set email alerts
|

Wind‐Driven Freshwater Export at Cape Farewell

Abstract: Increased freshwater input to the Subpolar North Atlantic from Greenland ice melt and the Arctic could strengthen stratification in deep convection regions and impact the overturning circulation. However, freshwater pathways from the east Greenland shelf to deep convection regions are not fully understood. We investigate the role of strong wind events at Cape Farewell in driving surface freshwaters from the East Greenland Current to the Irminger Sea. Using a high‐resolution model and an atmospheric reanalysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 64 publications
(92 reference statements)
0
19
0
Order By: Relevance
“…The salinity climatology (Figure 4a) shows different behavior in the upper and lower parts of the water column. In summer, the surface layer freshens, likely through precipitation and freshwater from the Greenland shelf (Duyck & De Jong, 2021; Duyck et al., 2022). The deeper part of the water column is dominated by lateral exchange with the perimeter of the Irminger Sea, where salinity is generally higher than in the DCA (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The salinity climatology (Figure 4a) shows different behavior in the upper and lower parts of the water column. In summer, the surface layer freshens, likely through precipitation and freshwater from the Greenland shelf (Duyck & De Jong, 2021; Duyck et al., 2022). The deeper part of the water column is dominated by lateral exchange with the perimeter of the Irminger Sea, where salinity is generally higher than in the DCA (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…They found that surface temperatures were high in a broad area near the southeast Greenland shelf, where glacier melt would be accelerated. Freshening due to ice melt is a plausible cause for freshwater anomalies near the East Greenland shelf, which we know can be exported to the DCA (Duyck & De Jong, 2021;Duyck et al, 2022;Foukal et al, 2020) and thus increase the stratification there. In 2019 runoff from Greenland was high was well (Slater et al, 2021), but there was also an additional cause for the high stratification: a strong freshwater anomaly that formed between 2012 and 2016 in the eastern subpolar North Atlantic, as described by Holliday et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…The high EKE region west of the DCA (Figure 2d) does not seem to generate eddies with a fresh cap that influence the Irminger Sea restratification. Either the EKE in this region is related to a circulation response to the wind that does not consist of coherent eddies (Duyck et al, 2022), or eddies formed in this region tend to move westward and will be quickly advected by the EGC, thus being unable to enter the convective region. As opposed to the Labrador Sea, in the Irminger Sea the upper layer freshening is due to surface freshwater gain and thin layers of freshwater driven off the East Greenland shelf during strong wind events (Duyck et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The salinity climatology (Figure 4a) shows different behavior in the upper and lower parts of the water column. In summer, the surface layer freshens, likely through precipitation and freshwater from the Greenland shelf (Duyck & De Jong, 2021;Duyck et al, 2022). The deeper part of the water column is dominated by lateral exchange with the perimeter of the Irminger Sea, where salinity is generally higher than in the DCA (Figure 2a).…”
Section: Structure and Variability Of Restratificationmentioning
confidence: 99%
“…While Castelao et al (2019) also showed that upwelling-favorable winds transport meltwater from the shelf into the WGC, the freshwater is subsequently fluxed into the interior basin by eddies. Additionally, recent modeling work along southeast Greenland and at Cape Farewell demonstrates that forward Greenland tip jets and westerly wind events flux a substantial amount of liquid freshwater across the shelfbreak at synoptic timescales east and south of Cape Farewell (Duyck et al, 2022).…”
mentioning
confidence: 99%